2017
DOI: 10.1111/febs.14273
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and functional analysis of cystathionine β‐synthase: an enzyme involved in the reverse transsulfuration pathway of Bacillus anthracis

Abstract: Structural data are available in the PDB under the accession number 5XW3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 66 publications
3
41
1
Order By: Relevance
“…Mutation of two of these residues in Saccharomyces cerevisiae CBS ( Sc CBS) resulted in a loss of activity with substrate L‐serine and a gain of activity with OAS. Earlier reports on OCBS (Hullo et al , ; Devi et al , ; Matoba et al , ) suggested OCBS to be present only in a few bacteria, but our study revealed the presence of OCBS in a greater variety of bacteria.…”
Section: Introductioncontrasting
confidence: 73%
See 4 more Smart Citations
“…Mutation of two of these residues in Saccharomyces cerevisiae CBS ( Sc CBS) resulted in a loss of activity with substrate L‐serine and a gain of activity with OAS. Earlier reports on OCBS (Hullo et al , ; Devi et al , ; Matoba et al , ) suggested OCBS to be present only in a few bacteria, but our study revealed the presence of OCBS in a greater variety of bacteria.…”
Section: Introductioncontrasting
confidence: 73%
“…We retrieved many protein sequences annotated either as cysteine synthase or OASS from the NCBI database using PSI‐BLAST with Bacillus anthracis OCBS as the search template (due to it having previously been shown to be an OCBS [Devi et al , ]). Most of these retrieved sequences probably corresponded to OCBS, with the product of the gene hp0107 of H. pylori being one of them.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations